Potential Use of Cinnamomum burmanii Essential Oil-based Chewing Gum as Oral Antibiofilm Agent - Mutma Inna; Novi Atmania; Septika Prismasari (Journal of Dentistry Indonesia, 2012)
Oral biofilm contributed to oral problem since it cause oral and teeth diseases such as caries, calculus, gingivitis and pe-riodontitis. Actions for overcoming these problems are needed. Currently, formation of oral biofilm is usually prevented by using mouthwash or toothpaste derived from synthetic materials. Increasing research on the use of natural resources has led to the innovation of finding antibiofilm product. Cinnamon is one of herb plants originated from Indonesia that has been known for its antibacterial and antibiofilm activities. These activities are owned by its essential oil. This review fo-cused on potential use of Cinnamomum burmanii’s essential oil as oral antibiofilm agent and looking at the possibility of its usage in chewing gum. DOI: 10.14693/jdi.v17i3.40